Model for Analysis of Internal Communication (MACIn): proposed visual instrument for qualitative research (Intercom - Brazilian Journal of Communication Sciences, 2023)
In this article we propose a model for a visual instrument that allows the analysis of communication within organizations, called the Model for Analysis of Internal Communication – MACIn. It is consists of six quadrants, five of which are anchored in the literature, and it is designed to assist in the diagnosis of communication management and the conduct of focus groups, whether for scientific or managerial purposes. MACIn combines the canvas model, the focus group technique and the topic of internal communication into a single tool. This tool allows the user to gather information and facilitate discussions on topics such as organizational goals, perceptions of internal communication, the channels used, information flows and access , and leadershipcommunication. This study highlights the agility that MACIn brings to the data collection process, and the possibility of interviewing different groups while maintaining the same approach, allowing for later comparative analysis.
Keywords: Organizational Communication; Internal Communication; Qualitative Research; Focus Group; Visual Model